2023
DOI: 10.1126/scitranslmed.adg9452
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of booster mRNA vaccination and SARS-CoV-2 Omicron infection on T cell immunity across immunocompromised states

Abstract: Suboptimal immunity to SARS-CoV-2 mRNA vaccination has frequently been observed in individuals with various immunodeficiencies. Given the increased antibody evasion properties of emerging SARS-CoV-2 subvariants, it is necessary to assess whether other components of adaptive immunity generate resilient and protective responses against infection. We assessed T cell responses in 279 individuals, covering five different immunodeficiencies and healthy controls, before and after booster mRNA vaccination, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Indeed, longitudinal analyses of immune-suppressed patients with diverse pathologies observe sharp declines in post-second dose responses, 29,51 whereas responses remain stable at similar magnitudes to healthy individuals following third and fourth doses. 28,51 Interestingly, although a fourth dose enhanced CD4 + responses compared with post-third dose levels, breakthrough infection did not further stimulate BA.4/5-specific T cells in patients who received a fourth dose, despite cases occurring during the Omicron wave of December 2021 to March 2022. However, these infections occurred >4 mo (IQR, 111-148 d) before 1-y sampling, thus the acute T cell response to infection was likely not captured.…”
Section: Table 1 (Continued)mentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, longitudinal analyses of immune-suppressed patients with diverse pathologies observe sharp declines in post-second dose responses, 29,51 whereas responses remain stable at similar magnitudes to healthy individuals following third and fourth doses. 28,51 Interestingly, although a fourth dose enhanced CD4 + responses compared with post-third dose levels, breakthrough infection did not further stimulate BA.4/5-specific T cells in patients who received a fourth dose, despite cases occurring during the Omicron wave of December 2021 to March 2022. However, these infections occurred >4 mo (IQR, 111-148 d) before 1-y sampling, thus the acute T cell response to infection was likely not captured.…”
Section: Table 1 (Continued)mentioning
confidence: 98%
“…The BA.4/5 and XBB.1.5 variants escape antibodymediated neutralization in individuals vaccinated against the ancestral strain. 13,[16][17][18][19][20]62 CD4 + and CD8 + T cell responses have thus far shown conserved cross-reactivity with Omicron 18,[26][27][28]63 including BA.4/5 in immune-compromised patients and SOTRs, 30,64 but no data existed for T cell responses to XBB.1.5. In contrast to previous research, we found small but significant decreases in T cell recognition of BA.4/5 relative to the ancestral strain.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the context of infection it is plausible that the relative importance of different compartments of the immune system shifts, and that viral control and clearance requires cellular immunity 1519 . While there has been clear evidence of acute and memory T cell responses to SARS-CoV-2 infection 2026 and COVID-19 vaccines 2734 , studies on protective roles of T cells have been limited in humans, particularly in non-hospitalized cases, given the technical difficulties of conducting large scale studies examining acute antigen-specific T cell responses and viral loads concomitantly in non-hospitalized individuals 19,3537 . There is evidence for cellular immunity contributing to SARS-CoV-2 protection in non-human primate models 18 .…”
Section: Mainmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) has resulted in an enormous societal burden, with a toll of millions of infections and deaths worldwide 1 . Immunocompromised patients who have undergone solid organ transplantation (SOT) are more susceptible to SARS-CoV-2 infection and produce less robust antibody responses following vaccination 2 , although they can achieve effective T cell responses with multiple vaccinations 3 . In addition, they are more likely to be hospitalized, experience adverse clinical outcomes, and have longer durations of infectiousness compared to the general population [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%